Study on machinability of in situ Al–4.5%Cu–TiC metal matrix composite-surface finish, cutting force prediction using ANN. (January 2016) - Das, Biswajit; Roy, Susmita; Rai, R.N.; Saha, S.C.
Abstract: This paper discusses the experimental exploration on chip formation, surface roughness and cutting force measurement throughout the CNC milling operation of Al–4.5%Cu/TiC MMCs produced by the in situ practice and compared the results with those for Al–4.5%Cu/SiC MMCs produced by ex situ technique and with Al–4.5Cu master alloy. The cutting forces were measured during the milling operation with the aid of a dynamometer, surface roughness was measured by using a 3D profilometer, the chips formed were also characterised and compared from the viewpoint of machinability. The present study also explores the potential of artificial neural network to predict the cutting force and surface roughness generated during machining in CNC milling machine.